Proton-transfer and hydrogen-bond interactions determine fluorescence quantum yield and photochemical efficiency of bacteriophytochrome - Toh, K. C. (National Academy of Sciences, 2010)
Phytochromes are red-light photoreceptor proteins that regulate a variety of responses and cellular processes in plants, bacteria, and fungi. The phytochrome light activation mechanism involves isomerization around the C15═C16 double bond of an open-chain tetrapyrrole chromophore, resulting in a flip of its D-ring. In an important new development, bacteriophytochrome (Bph) has been engineered for use as a fluorescent marker in mammalian tissues. Here we report that an unusual Bph, RpBphP3 from Rhodopseudomonas palustris, denoted P3, is fluorescent. This Bph modulates synthesis of light-harvesting complex in combination with a second Bph exhibiting classical photochemistry, RpBphP2, denoted P2. We identify the factors that determine the fluorescence and isomerization quantum yields through the application of ultrafast spectroscopy to wild-type and mutants of P2 and P3. The excited-state lifetime of the biliverdin chromophore in P3 was significantly longer at 330–500 ps than in P2 and other classical phytochromes and accompanied by a significantly reduced isomerization quantum yield. H/D exchange reduces the rate of decay from the excited state of biliverdin by a factor of 1.4 and increases the isomerization quantum yield. Comparison of the properties of the P2 and P3 variants shows that the quantum yields of fluorescence and isomerization are determined by excited-state deprotonation of biliverdin at the pyrrole rings, in competition with hydrogen-bond rupture between the D-ring and the apoprotein. This work provides a basis for structure-based conversion of Bph into an efficient near-IR fluorescent marker.